2023
DOI: 10.3899/jrheum.2023-0219
|View full text |Cite
|
Sign up to set email alerts
|

For Your Eyes Only: 007 Tips for the Management of Cardiovascular Risk Factors in Antineutrophil Cytoplasmic Antibody–Associated Vasculitis

Abstract: Premature atherosclerosis has been observed during the course of different systemic inflammatory diseases, such as rheumatoid arthritis (RA), systemic lupus erythematosus, and antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV).1-3As a result, cardiovascular (CV) events, including myocardial infarction, stroke, heart failure, coronary artery disease, and death, occur 1.65 to 3 times more commonly in patients with AAV as compared to the general population, and the risk appears to be highest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…[ 36 , 37 ] Previous studies have indicated that patients with AAV have an elevated risk of experiencing cardiovascular events. [ 38 , 39 ] Several studies have identified that cardiac involvement is a strong predictor of mortality in AAV, which is consistent with our results. [ 12 , 40 ] Our study focused on the prognosis of AAV-ILD.…”
Section: Discussionsupporting
confidence: 92%
“…[ 36 , 37 ] Previous studies have indicated that patients with AAV have an elevated risk of experiencing cardiovascular events. [ 38 , 39 ] Several studies have identified that cardiac involvement is a strong predictor of mortality in AAV, which is consistent with our results. [ 12 , 40 ] Our study focused on the prognosis of AAV-ILD.…”
Section: Discussionsupporting
confidence: 92%